Prioritizing preferred traits in the yam value chain in Nigeria: a gender situation analysis - Okoye, B.; Ofoeze, M.; Ejechi, M.; Onwuka, S.; Nwafor, S.; Onyemauwa, N.; Ukeje, B.; Eluagu, C.; Obidiegwu, J.; Olaosebikan, O.; Madu, Tessy (Frontiers Media, 2023)
This study describes what did and did not work in the prioritization of preferred traits within the value chain of yam and associated food products (boiled and pounded yam) in Nigeria. Demand-led breeding protocols have enhanced participatory methods along gender lines to increase the clarity of information on the yam traits preferred by farmers and other end users. Drawing on the experience of the cross-cutting gender team at the National Root Crops Research Institute (NRCRI), Umudike, and partners, this study documents the successes and constraints in the use of gender-inclusive approaches for effective breeding. Methods in our gender studies involve critical assessment of the distinction between quantitative and qualitative research, with particular attention to measurement. Various techniques for data collection, such as interviews, observation, and archival studies, are assessed to locate their potential for constructing successful research projects. The methods used include participatory varietal selection, participatory plant breeding, focused discussions with farmer groups, value chain mapping, G+ tools, trait preferences (processing and consumption), triangulation of multi-disciplinary datasets, and social survey research. Yam production in southeast Nigeria is dominated by men, while women are the main processors. Gendered power play, access to resources, and decision-making have been found to constrain women's participation in yam production (and in yam research). Sex disaggregation was applied within the value chain studies to capture the complementarity and differences in the perceptions of women and men. The methods used facilitated the development and release to farmers in 2023 of three improved yam varieties with consumer-preferred characteristics such as high yield, high dry matter content, white tubers, and good boiling and pounding capability. The success stories also show that effective communication and cooperation within the gender cross-cutting team and farmer groups are important for better results. When gender specialists, food scientists, and breeders work together, innovations are created, challenges are overcome, and information is shared.